Intrahepatic Cholangiocarcinoma Cells Promote Epithelial-mesenchymal Transition of Hepatocellular Carcinoma Cells by Secreting LAMC2 - Cen, Wenda (J Cancer, 2021)
Hepatocellular carcinoma and intrahepatic cholangiocarcinoma cells are common primary hepatic tumor cells in the liver. Combined hepatocellular cholangiocarcinoma (CHC) contains both hepatocellular carcinoma cells and intrahepatic cholangiocarcinoma cells in one tumor lesion and these tumors show poor prognosis. Here we examined the potential interaction between hepatocellular carcinoma cells and intrahepatic cholangiocarcinoma cells using cell culture studies. The results showed that culture supernatant from intrahepatic cholangiocarcinoma cells induced endothelial-mesenchymal transition and facilitated the migration and invasion of hepatocellular carcinoma cells, although it did not accelerate the proliferation of hepatocellular carcinoma cells. Furthermore, culture supernatant from intrahepatic cholangiocarcinoma cells increased the chemoresistance of hepatocellular carcinoma cells. Laminin subunit gamma 2 (LAMC2) was detected in the culture supernatant of intrahepatic cholangiocarcinoma cells but not in that of hepatocellular carcinoma cells. Using established LAMC2 knockout intrahepatic cholangiocarcinoma cells, our results demonstrated that intrahepatic cholangiocarcinoma cells promoted the epithelial-mesenchymal transition of hepatocellular carcinoma cells through secreting LAMC2. Our results have revealed a novel mechanism of interaction between intrahepatic cholangiocarcinoma cells and hepatocellular carcinoma cells, which may provide new insight into developing effective treatments for CHC.